2005
DOI: 10.1016/j.orthres.2004.03.003
|View full text |Cite
|
Sign up to set email alerts
|

An articulated antibiotic spacer used for infected total knee arthroplasty: A comparative in vitro elution study of Simplex® and Palacos® bone cements

Abstract: For the staged management of infected total knee arthroplasty (TKA), antibiotic laden polymethylmethacrylate (PMMA) spacers have been recommended. Antibiotic-impregnated PMMA spacers target drug delivery, achieving high local levels while limiting the potential for host toxicity associated with parenteral antimicrobial therapy. This study examined the elution characteristics of an articulating PMMA TKA spacer that has been useful clinically. Tobramycin and vancomycin are both active against many organisms lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 21 publications
2
103
1
Order By: Relevance
“…Our data showing a local tissue concentration of antibiotics in excess of the MIC, even after 6 weeks of implantation, are consistent with data from the few studies analyzing antibiotic levels around the spacer in vitro or aspirates after several weeks [4,21,32]. Moreover the low rate of recurrence of infection with a two-stage approach supports the conclusion that the spacer releases sufficient, high amounts of antibiotics after that interval to treat infection and is not just fulfilling a physical, jointmaintaining function [9,10,25].…”
Section: Discussionsupporting
confidence: 90%
“…Our data showing a local tissue concentration of antibiotics in excess of the MIC, even after 6 weeks of implantation, are consistent with data from the few studies analyzing antibiotic levels around the spacer in vitro or aspirates after several weeks [4,21,32]. Moreover the low rate of recurrence of infection with a two-stage approach supports the conclusion that the spacer releases sufficient, high amounts of antibiotics after that interval to treat infection and is not just fulfilling a physical, jointmaintaining function [9,10,25].…”
Section: Discussionsupporting
confidence: 90%
“…Lastly, this work would be furthered by testing other types of PMMA monomer, which have been reported to have different elution characteristics and pore size. 19 In addition, various concentrations and combination of antibiotics in different cements should also be tested.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro studies have demonstrated that many commonly used antibiotics are released from PMMA bone cement with a very high initial rate of drug delivery followed a rapid decline over a few days. [12][13][14][15] The articulating antibiotic PMMA spacers, however, are essentially different from the beads. The spacers have a cement-on-cement bearing surface, and obviously have a much smaller surface area to volume ratio.…”
Section: Introductionmentioning
confidence: 99%